Mortality from necrotizing fasciitis: a cross-sectional study - Paul, Patric; Prabhakaran, Induprabhayadev; Chisthi, Meer (International Surgery Journal, 2020)
Background: Necrotizing fasciitis refers to the rapidly progressive inflammation of the fascia, with secondary necrosis of subcutaneous tissues. Due to the high mortality, it is considered a surgical emergency, needing timely diagnosis and appropriate treatment with early debridement. The aim of the study was to analyse the clinical profile of patients with necrotizing fasciitis so as to determine the mortality and the risk factors associated with mortality and other poor outcomes. Methods: This retrospective cross-sectional study was conducted in a tertiary hospital in Kerala, from January 2016 through January 2018. 175 cases were identified through the ICD codes for necrotizing fasciitis and Fournier’s gangrene in the discharge and death registers; and data were obtained about these patients. The data were analyzed to assess the study objectives. Results: In this study mortality was found to be 22.7%. Diabetes mellitus was found to be the most common co-morbid disease and had a significant association with increased risk of amputation. Mixed growth (type I NF) was the most common microbiological isolate and Pseudomonas was the most common gram-negative isolate. 4 cases of MRSA were recorded. Klebsiella infection was found to have increased risk of undergoing limb amputation. 7.4% of the patients required amputation during hospital stay for infection control. Conclusions: Necrotizing fasciitis has a high mortality. Diabetes mellitus was found to be the most common co-morbid disease. Increased blood glucose and low serum albumin had a significant association with an increased risk of amputation. Proper control of these factors is essential to reduce mortality from this condition.